Volatile-Mediated Attraction of Greenhouse Whitefly Trialeurodes vaporariorum to Tomato and Eggplant - Darshanee, Hewa L. C.; Ren, Hui; Ahmed, Nazeer; Zhang, Zhan-Feng; Liu, Yan-Hong; Liu, Tong-Xian (Frontiers in Plant Science, 2017)
The behavior of the greenhouse whitefly, Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae), is known to be affected by plant volatile cues, but its attraction or repellent to specific volatile cues has not been deeply studied yet. Therefore, the aim of our study was to identify the most attractive plant among cultivars of tomato (Solanum lycopersicum) and eggplant (Solanum melongena) to evaluate the volatiles of plants to identify the chemical compound(s) that attract T. vaporariorum. We speculated that whitefly–host plant interaction primarily depends on plant volatile emissions and that once the plant is damaged, it might attract more whiteflies. Three intact (uninfested) tomato, four intact eggplant cultivars and whitefly infested plants of the most whitefly attractive tomato and eggplant cultivars were examined by behavioral assay experiments for attractiveness to T. vaporariorum and headspace volatile were determined by solid-phase microextraction (SPME) and gas chromatography-mass spectrometry. Whiteflies had the highest preference for the intact eggplant Kuai Yuan Qie (KYQ) among the eggplant and the tomato plant cultivars in bioassay experiments. Although both male and female whiteflies were significantly more attracted to infested KYQ plants than to intact plants, whitefly females did not select conspecific-infested YG plants. The volatile emissions among different plant cultivars in individual species and infested versus intact plants were significantly different. Among these volatiles, identified major green leaf volatiles [(Z)-3-hexen-1-ol] and terpenoids [α-pinene, (E)-β-caryophyllene, α-humulene, azulene] showed a constitutive relationship with the most whitefly preference plants. Our findings provide new insights into the chemical compounds that attract or repel whiteflies.